Successfully Implementing Microsoft Dynamics by Using the Regatta® Approach for Microsoft Dynamics - Koop, Reinder; Muris, Esther; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Does the implementation of Microsoft Dynamics contribute to the goals of your company? Does your company itself have the capacity to build a bridge between the Business and IT? Can your employees adopt a flexible attitude on all the related changes ? And, probably even more important, is that what they are also willing to do? If you are striving for a full-hearted yes to these questions, this is the book for you. Regatta Dynamics, our methodology for the structured implementation of Microsoft Dynamics, is based on our firm belief that when you implement Microsoft Dynamics there must be a balance between the Business and IT. The consistency and cohesion between the different underlying work streams are hereby of overriding importance for the ultimate result. In this book, we answer the questions mentioned above and describe pragmatically the full implementation process from A to Z. Emphasis is placed on the organizational component of the implementation process and the cohesion with functional and technical processes. In our opinion, by involving the organization properly during the change process, your company can benefit much more and much faster from Microsoft Dynamics. Next to being a blueprint for the implementation complexity, this book can also be used as a guideline for daily practice. This book is therefore interesting for project - and line managers, key-users, IT-managers and implementation consultants. The authors are both working in the field of implementation. While writing this book they have drawn from their many years of experience in this field within Sogeti Netherlands. Wherever possible the authors have tried to change every challenge from unmanageable to comprehensive and, based on clearly separated sequences, the pluriform reality of implementation has been reduced to acceptable proportions that can be planned and managed. Main goal to achieve is to continuously create a tangible and remarkably better result for organizations who are considering implementing Microsoft Dynamics.
Background and Theory -- Implementing Microsoft Dynamics -- The Regatta for Dynamics Model -- Regatta for Dynamics in Practice -- Model Process Cluster -- Map Process Cluster -- Customize Process Cluster -- Integrate Process Cluster.
Keywords: Computer science; Management; Industrial management; Information technology; Business -- Data processing; Application software; Management information systems; Computer Science; Management of Computing and Information Systems; IT in Business; Information Systems Applications (incl. Internet).; Innovation/Technology Management; Computer Appl. in Administrative Data Processing; Electronic books